A study to assess common morbidity pattern of an urban population of Tripura - Datta, Anjan; Nag, Kaushik; Karmakar, Nabarun; Datta, Srabani (International Journal Of Community Medicine And Public Health, 2017)
Background: To plan for effective health measures, knowledge regarding morbidity profile of local area is very important. Preventive health strategies cannot be made without an idea about the disease burden and changing trend of diseases of the locality. Keeping this background in mind the present study was conducted. The objective of the study was to assess the common morbidity pattern of people living in an urban area of Tripura. Methods: A community based cross-sectional study was conducted among people living in the filed practice area of Urban Health Training Centre, Dukli under Department of Community Medicine, Tripura Medical College & DR. BRAM Teaching Hospital, Hapania for a period of one year. Five hundred fourty participants were selected using simple random sampling technique and data was collected using a pre-designed pretested questionnaire and analyzed using SPSS version 20.0 software. Results: Majority (50.93%) of the study participants were females and belonged to 19-59 years age group (32.78%). The commonest type of morbidity was found to be acute respiratory infections (31.10%), followed by musculo-skeletal disorders (17.78%), with non-communicable diseases like diabetes mellitus, hypertension, obesity etc. catering 13.70% of all morbidities. Majority of the participants were having single morbidity (55.74%) than those having comorbidities. Conclusions: There is dual burden of communicable as well a non-communicable diseases in our study population. Future studies for risk factors assessment are required to plan for effective preventive strategies locally.